TI_GERICHTE 60.2009.427 vom 20. April 2010 , Istanza di indennità per ingiusto procedimento. accusato prosciolto - TI Tribunale d'appello (2010)
Istanza di indennità per ingiusto procedimento. accusato prosciolto